2004
DOI: 10.1542/peds.113.5.e440
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Thrive and Cognitive Development in Toddlers With Infantile Anorexia

Abstract: ABSTRACT. Objective. The goal of this study was to examine the relative contributions of growth deficiency and psychosocial factors to cognitive development in toddlers with infantile anorexia.Methods. Eighty-eight toddlers, ranging in age from 12 to 33 months, were enrolled in this study. Toddlers were evaluated by 2 child psychiatrists and placed into 1 of 3 groups: infantile anorexia, picky eater, and healthy eater. All 3 groups were matched for age, race, gender, and socioeconomic status (SES). Toddlers un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 28 publications
3
33
0
10
Order By: Relevance
“…A hallmark is conflict between parent and child, which if unresolved may hinder the child's ability to reach his or her optimal cognitive potential. 34 This reflects conflict in the home environment, rather than low nutrient intake. 35 The Apathetic, Withdrawn Child These children are inactive, disinterested both in eating and their environment, and communicate poorly with their caregivers.…”
Section: Misperceivedmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallmark is conflict between parent and child, which if unresolved may hinder the child's ability to reach his or her optimal cognitive potential. 34 This reflects conflict in the home environment, rather than low nutrient intake. 35 The Apathetic, Withdrawn Child These children are inactive, disinterested both in eating and their environment, and communicate poorly with their caregivers.…”
Section: Misperceivedmentioning
confidence: 99%
“…1,2 The major concern for them is not their nutrition, 1,3,46 but family discord centered around coercive feeding and subsequent behavioral consequences. Chatoor et al 34 reported that conflict around feeding resulted in a lower Bayley Mental Developmental Index independent of the child's nutritional status. In a study of children defined by their parents as picky, Jacobi et al 2 showed a higher incidence of subsequent behavioral problems, including anxiety, depression, aggression, and delinquency.…”
Section: Misperceptionmentioning
confidence: 99%
“…4,7 Problematic eating and feeding behaviors are sources of concern for parents, and if prolonged can lead to weight loss or failure to gain weight and cognitive and developmental delay. [8][9][10] Feeding difficulties in healthy children are linked to a variety of causes, including environmental disruption, parental incompetence, the child's temperament, and psychological factors. It has been shown that certain characteristics of the infant combined with certain vulnerabilities in the parent lead to negative responses and conflict in their interactions.…”
mentioning
confidence: 99%
“…Seventeen feeding (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) studies with infant samples were identified (Table 1). Previouslypublished reviews have described methods commonly used to analyze eating behavior in infancy, both subsequent to (40) and during the weaning period (41).…”
Section: Feeding Studies In Infancymentioning
confidence: 99%
“…Chatoor and colleagues have used feeding paradigms to identify specific aberrant eating patterns. Their methodology involves mother-child feeding interactions that are videotaped and then coded by researchers to assess positive and negative feeding behaviors exhibited by both the mother and infant (32)(33)(34)(35). For example, a researcher may code a mother-infant feeding interaction as "dyadic reciprocity," a term that reflects positive mother-infant exchanges, or as "struggle for control," which is represented by the mother overriding the child's cues or child rejecting the food.…”
mentioning
confidence: 99%